Remarks on 'A comparative study of two types of ball-on-ball collision'. (28th November 2017) - Cross, Rod
Abstract: This comment addresses some points in the paper by White (2017 Phys Ed .52 045013). Specifically, we clarify the value for the coefficient of restitution, which we believe to be much lower than that obtained by White.